A combined approach of multiple-criteria decision analysis and discrete-event simulation: lessons learned from a fleet composition study. (14th April 2020) - Faria, Luis Filipe Figueira De; Asevedo, Luíze Fernandes De; Vieira, José Geraldo Vidal; Silva, João Eduardo Azevedo Ramos Da
This study proposes a framework for a decision of the fleet composition problem based on a set of qualitative and quantitative criteria, which is a hybrid method for decision-making support that combines MCDA and simulation techniques in a multicriteria scenario for fleet composition. The proposed framework is able, using simulations, to address the complexity of criteria considered in a fleet composition problem in order to increase the preciseness of the decision-making process. From the solutions evaluated, there was a change in the preference of the alternative initially chosen after simulation, which is considered to refine the solution provided by the MCDA method. Considering only the MCDA method, the cost is prioritised and the solution uses exclusively high capacity trucks. Using the simulation and a different weighing process, the service level has a greater importance and a percentage of smaller trucks is admitted as part of the fleet.